Review. Monitoring the intermodal, refrigerated transport of fruit using sensor networks - Ruiz-Garcia, L.; Barreiro, P.; Rodríguez-Bermejo, J.; Robla, J.I. (Spanish Journal of Agricultural Research, 2007)
Most of the fruit in Europe is transported by road, but the saturation of the major arteries, the increased demand for freight transport, and environmental concerns all indicate there is a need to change this means of transport. A combination of transport modes using universal containers is one of the solutions proposed: this is known as intermodal transport. Tracking the transport of fruit in reefer containers along the supply chain is the means by which product quality can be guaranteed. The integration of emerging information technologies can now provide real-time status updates. This paper reviews the literature and the latest technologies in this area as part of a national project. Particular emphasis is placed on multiplexed digital communication technologies and wireless sensor networks.